PENGARUH NON PERFORMING LOAN, CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS - Steven, .; Silvia, .; Sinaga, Jholant Bringg Luck Amelia Br; Januardin, . (Universitas Sam Ratulangi, 2018)
This research had purpose to determined the effect of NPL, CAR and LDR on Profitability in banking sector company listing in Indonesia Stock Exchange in years 2013-2017. The population of this research is banking sector company listing in Indonesia Stock Exchange over the period 2013-2017. Techniques used in the sample is Purposive Sampling, so obtained sample of 27 companies. The hypothesis results simultaneously shows NPL, CAR and LDR affect the Profitability in banking sector company listing in Indonesia Stock Exchange in years 2013-2017. The hypothesis results partially shows NPL negative affect and significant the Profitability in banking sector company listing in Indonesia Stock Exchange in years 2013-2017, CAR and LDR positive affect and significant the Profitability in banking sector company listing in Indonesia Stock Exchange in years 2013-2017.Keywords : NPL, CAR, LDR, Profitability, Banking Sector Company